3D microstructural architecture of muscle attachments in extant and fossil vertebrates revealed by synchrotron microtomography - Sanchez, S.; Dupret, V.; Tafforeau, P.; Trinajstic, Kate; Ryll, B.; Gouttenoire, P.; Wretman, L.; Zylberberg, L.; Peyrin, F.; Ahlberg, P. (Public Library of Science, 2013)
Background: Firm attachments binding muscles to skeleton are crucial mechanical components of the vertebrate body. These attachments (entheses) are complex three-dimensional structures, containing distinctive arrangements of cells and fibre systems embedded in the bone, which can be modified during ontogeny. Until recently it has only been possible to obtain 2D surface and thin section images of entheses, leaving their 3D histology largely unstudied except by extrapolation from 2D data. Entheses are frequently preserved in fossil bones, but sectioning is inappropriate for rare or unique fossil material. Methodology/Principal Findings: Here we present the first non-destructive 3D investigation, by propagation phase contrast synchrotron microtomography (PPC-SR µ CT), of enthesis histology in extant and fossil vertebrates. We are able to identify entheses in the humerus of the salamander Desmognathus from the organization of bone-cell lacunae and extrinsic fibres. Statistical analysis of the lacunae differentiates types of attachments, and the orientation of the fibres, reflect the approximate alignment of the muscle. Similar histological structures, including ontogenetically related pattern changes, are perfectly preserved in two 380 million year old fossil vertebrates, the placoderm Compagopiscis croucheri and the sarcopterygian fish Eusthenopteron foordi. Conclusions/Significance: We are able to determine the position of entheses in fossil vertebrates, the approximate orientation of the attached muscles, and aspects of their ontogenetic histories, from PPC-S µCT data. Sub-micron microtomography thus provides a powerful tool for studying the structure, development, evolution and palaeobiology of muscle attachments.